Predictors of protean career behavior and moderating role of career strategies among professionals in the Malaysian electrical and electronics industry - Wong, Siew Chin (2015)
The present study is aimed to investigate the predictors of protean career behavior and the moderating roles of career strategies among professional employees in E&E industry. The concept of protean career behavior transferred the responsibility from the organization to the individual in managing their career development. Basically, new career concept of protean career behavior is featured with non-linearity as compared with traditional career. Individual is viewed as “agent of their own career destinies”. Hence,this study examines how individuals predisposition to shape their careers, as well as the specific external environmental factors to affect individual career planning and management. Investigating this process is both theoretical and practically significant to provide better understanding of career-related behavior. This study employed Social Cognitive Career Theory (SCCT), extended SCCT, Job Characteristics Model (JCM),integrative model of job design and proactive behaviour as well as career dynamic model of reactions in order to provide an integrative and dynamic theoretical framework in explaining protean career behavior among professional employees in E&E industry. This study extends SCCT model by integrating job-related factors in predicting protean career behavior. Further, the present study aimed to examine the moderating role of career strategies on the relationship between independent variables (e.g., individual, organizational and job-related factors) and protean career behavior among professional employees in E&E industry. The findings indicated the level of protean career behavior was high among 306 respondents from E&E industry. The result in the PLS-SEM path models revealed that self-efficacy, outcome expectation, goal orientation, internal locus of control and external locus of control (individual-related variables), employability culture (organizational-related variable) and job autonomy (job-related variable) were positively associated with professional employees’ protean career behavior. In contrast,there were no significant relationship among mentoring (organizational-related variable),task significance and job feedback (job-related variables) towards professional employees’ protean career behavior. Furthermore, the findings also indicated that goal orientation, employability culture and mentoring explained professional employees’protean career behavior differently for high and low level usage of career strategies. The findings of this study confirmed Social Cognitive Career Theory (SCCT) that proximal contextual elements (i.e., career strategies) would moderate the relationship between goal orientation (individual-related variable), employability culture and mentoring (organizational-related variables) on protean career behavior. This study provides a predictive framework explaining protean career behavior among professionals in E&E industry. The findings of the study also would assist individual, HRD practitioners and organization in understanding the issues and prospects of protean career behavior in the workplaces.